A qualitative study of patients' feedback about Outpatient Parenteral Antimicrobial Therapy (OPAT) services in Northern England: implications for service improvement. Issue 1 (10th January 2018) - Twiddy, Maureen; Czoski Murray, Carolyn J; Mason, Samantha J; Meads, David; Wright, Judy M; Mitchell, Elizabeth D; Minton, Jane
Abstract : Objective: Outpatient parenteral antimicrobial therapy (OPAT) provides opportunities for improved cost savings, but in the UK, implementation is patchy and a variety of service models are in use. The slow uptake in the UK and Europe is due to a number of clinical, financial and logistical issues, including concern about patient safety. The measurement of patient experience data is commonly used to inform commissioning decisions, but these focus on functional aspects of services and fail to examine the relational aspects of care. This qualitative study examines patients' experiences of OPAT. Design: In-depth, semistructured interviews. Setting: Purposive sample of OPAT patients recruited from four acute National Health Service (NHS) Trusts in Northern England. These NHS Trusts between them represented both well-established and recently set-up services running nurse at home, hospital outpatient and/or self-administration models. Participants: We undertook 28 semistructured interviews and one focus group (n=4). Results: Despite good patient outcomes, experiences were coloured by patients' personal situation and material circumstances. Many found looking after themselves at home more difficult than they expected, while others continued to work despite their infection. Expensive car parking, late running services and the inconvenience of waiting in for the nurse to arrive frustrated patients, while efficient services, staffed by nurses with the specialist skills needed to manage intravenous treatment had the opposite effect. Many patients felt a local, general practitioner or community health centre based service would resolve many of the practical difficulties that made OPAT inconvenient. Patients could find OPAT anxiety provoking but this could be ameliorated by staff taking the time to reassure patients and provide tailored information. Conclusion: Services configurations must accommodate the diversity of the local population. Poor communication can leave patients lacking the confidence needed to be a competent collaborator in their own care and affect their perceptions of the service.